Instantaneous deflection calculation for steel fibre reinforced concrete one way members. (15th January 2017) - Amin, Ali; Foster, Stephen J.; Kaufmann, Walter
Highlights: A simple model is analytically derived to predict the instantaneous deflection of steel fibre reinforced concrete (SFRC) one way members. The model considers the beneficial effect of the steel fibres to the tension stiffening capacity of SFRC members. The model is shown to compare well with test data obtained from the literature. Abstract: In this paper, a simple yet accurate method for determining the instantaneous deflection of steel fibre reinforced concrete (SFRC) one way members is presented. The model builds upon previous work conducted by the authors by considering the beneficial effect of the fibres across a crack to the tension stiffening relationship of SFRC. In turn, the increased stiffness across the crack is translated into curvature and then to deflection. The model reported herein is founded upon a previously reported adaptation of the Tension Chord Model of Marti et al. (1998) for the prediction of deflections for RC beams and is shown to provide good correlations to test data.